Eyes Can Switch Finger Stroke. (June 2013) - Oh, Songjoo
In this study it is demonstrated that what visually appear to be strokes on the index finger can be felt as real despite the fact that the synchronous actual stroke is being carried out on a different finger that is occluded from sight. This illusory stroke effect was stronger between the middle and index fingers than was the case between the index and other fingers. This illusion clearly shows that the synchronized input of visual and tactile cues can induce the tactile mislocalization of a body part even at the tactile localization's suprathreshold intensity and that, furthermore, the strength of the effect depends on the anatomical proximity between the body parts involved.